How to Calculate Adsorption Isotherms of Particles Using Two-Parameter Monolayer Adsorption Models and Equations - Risti Ragadhita; Asep Bayu Dani Nandiyanto (Indonesian Journal of Science and Technology, 2021)
Adsorption isotherm is the most important calculation to predict and analyze the various possible mechanisms that occur in adsorption process. However, until now, most studies only presented the adsorption isotherm theory, and there are no studies that explain the adsorption isotherm thoroughly and in detail from theory to calculation. Therefore, this study contains guidelines for selecting the type of adsorption isotherm to describe the entire adsorption data set, which is featured by the ten most common adsorption isotherms. The steps of how to analyze the two-parameter monolayer adsorption are presented. This study is expected to provide clear and useful information for researchers who are working and studying on the adsorption process.